Low level of serum total cholesterol predicts mortality in early-stage multiple system atrophy: a prospective-cohort study - Huang, Jingxuan; Zhang, Lingyu; Jiang, Qirui; Wang, Shichan; Xiao, Yi; Che, Ningning; Lin, Junyu; Zhao, Bi; Cheng, Yangfan; Li, Chunyu; Shang, Huifang (Frontiers in Nutrition, 2025)
BackgroundSerum total cholesterol (TC) is associated with the risk of multiple system atrophy (MSA). However, the potential impact of the serum TC levels on the mortality of patients with MSA remains to be elucidated. The study aims to clarify the association between baseline level of serum TC and survival of patients with early MSA.MethodsA total of 364 patients with MSA were recruited and assessed at baseline and follow-up. Patients with MSA were stratified into three groups based on the serum TC tertiles. The role of serum TC on survival was analyzed using Kaplan–Meier survival analysis and Cox regression models. Restricted Cubic Spline regression was employed to investigate the non-linear relationship between serum TC levels and survival.ResultsDuring a median follow-up period of 4.75 years, the survival duration of patients with MSA was shorter in the lowest serum TC group compared to the other two groups (Log-rank p = 0.004). In the multivariable Cox regression model, individuals in the intermediate serum TC group demonstrated a reduced mortality compared to those in the lowest group (HR: 0.47; 95% CIs: 0.23–0.96). There was a non-linear relationship between serum TC level and survival with the lowest risk of death at the value of 4.38 mmol/L.ConclusionSerum TC level at baseline negatively correlated with survival of patients with MSA. Serum TC emerges as a significant predictor of mortality in patients with early-stage MSA.